O mal-estar docente e os limites da experiência no tempo presente: uma leitura frankfurtiana - Manfré, Ademir Henrique [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This research aims at discussing the topic of the instructor’s inquietude and its relations to the formative activity. From a theoretical approach, this research is part of the Graduation Program in Education of FCT/UNESP/Campus of Presidente Prudente/SP, more specifically of the research line on “Formative process, differences and values”. To investigate our topic we assume the assumption that the instructor’s inquietude is due to the process of expropriation of the experience in nowadays. From this, we investigate what is the instructor’s inquietude so that clarifying its meaning. One of the intentions of this research was to think about the contradictions produced by Modernity in relation to its proposal for cultural formation (Bildung). Initially, we make some considerations in respect of the implication of the educational debate on instructor’s inquietude to motivate the reflection about the poorness of experience in nowadays. In a second moment, we discuss the main Freudian thesis, and of others contemporary experts, about the “Civilizations and its Discontents” as an inherent process to the constitution of subjectivities. Finally, our central worry in this work was to think about the challenges posed in nowadays to the achievement of an education based in a formative experience. In this context, we reflected about the importance of conceive the paths for a compromised education with the formation of autonomous individuals, which are able to seek for its own identity, giving a (new) meaning to the perception of reality via its experience. In summary, we saw in the Critical Theory a philosophical-theoretical referential that contemplates the possibility for the development (in different basis) of an analysis of the social process in which is inserted the school education in nowadays, as well its relations to the productions of the instructor’s inquietude.

Esta pesquisa, de natureza teórica, está vinculada à linha de pesquisa “Processos formativos, diferença e valores” do Programa de Pós-graduação em educação da FCT/UNESP/Campus de Presidente Prudente/SP e discute o tema do mal-estar docente e seus vínculos com a formação. Para tanto, partimos da suposição de que o mal-estar docente é decorrente do processo de expropriação da experiência no tempo presente. Desse modo, tivemos como objetivo principal investigar em que consiste o mal-estar docente, clarificando o seu sentido. Uma das intenções da presente pesquisa foi refletir sobre as contradições geradas pela modernidade no que se refere à sua proposta de formação cultural (Bildung). Inicialmente, tecemos considerações a respeito das implicações do debate educacional acerca da temática mal-estar docente para se pensar a pobreza da experiência na atualidade. Posteriormente, discutimos as principais teses freudianas e de autores contemporâneos com relação ao “mal-estar na civilização” como processo inerente à constituição das subjetividades. Por fim, nossa preocupação foi pensar nos desafios postos pela atualidade para a realização de uma educação com base em uma experiência formativa. Nesse contexto, refletimos sobre a importância de se conceber os caminhos de uma educação comprometida com a formação dos indivíduos autônomos, capazes de buscar a sua identidade, re-significando a percepção da realidade pela via dessa mesma experiência. Enfim, vimos na Teoria Crítica um referencial teórico-filosófico que contempla a possibilidade de desenvolvermos em bases diferentes a análise do processo social em que se insere a educação escolar na atualidade bem como seus vínculos com a produção do mal-estar docente.
Keywords: Educação; Formação profissional; Antropologia educacional; Professores - Experiencias; Education